Eksplorasi Etnomatematika pada Batu Dolmen di Situs Duplang Desa Kamal Jember - Rahayu, Diana Putri; Putra, Eric Dwi; Sulisawati, Dwi Noviani (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The main focus of this research is to identify geometric patterns that may be hidden within the dimensions, shapes, and orientations of the dolmens. Overall, the objective is to identify, analyze, and understand the ethnomathematical concepts embedded in the dolmens at the Duplang Site. The specific aims include documenting the dimensions, comparing them with other sites, and interpreting their cultural significance. This study employs a qualitative descriptive method with an ethnographic approach. The research methods involve direct observation, documentation, interviews, visual analysis, and precise measurements using a measuring tape. The outcomes of this exploration are expected to make a significant contribution to our understanding of the cognitive abilities of prehistoric communities. The main outputs include a comprehensive research report and the identification of unique mathematical patterns such as hidden geometries